Analysis of the socioeconomic and productive profile of rural properties with succession in different regions of the State of Rio Grande do Sul, Brazil (Research, Society and Development, 2020)
Generational succession, a process of transferring management and rural properties, takes place intergenerationally, especially between parents and children. For this process to happen there are a series of conditions that will influence the decision of young people to remain or not on the property. Among them, the very conditions of rural properties, such as economic issues that are related to obtaining satisfactory, productive income, related to the activities carried out on the properties, and infrastructure, related to the availability of machinery and equipment, as well as land area. Therefore, this article aims to characterize the profile of properties that have succession or succession perspectives, considering two distinct regions of the state of Rio Grande do Sul, Northwest and Central Oriental. In general, the results showed that young people from both regions and according to the particularities of the activities they develop enjoy a satisfactory income, access to capital, technologies and equipment on the property, which thus contributes to their stay in the country. countryside.